Clinical, radiographic, ultrasonographic and computed tomographic features of nonseptic osteitis of the axial border of the proximal sesamoid bones. (5th December 2013) - Vanderperren, K.; Bergman, H. J.; Spoormakers, T. J. P.; Pille, F.; Duchateau, L.; Puchalski, S. M.; Saunders, J. H.
Summary Reasons for performing study Lysis of the axial aspect of equine proximal sesamoid bones (PSBs) is a rare condition reported to have septic or traumatic origins. Limited information exists regarding imaging of nonseptic axial osteitis of a PSB. Objectives To report the clinical, radiographic, ultrasonographic, computed tomographic and intra‐arterial contrast‐enhanced computed tomographic abnormalities in horses with axial nonseptic osteitis of a PSB. Study design Retrospective clinical study. Methods Eighteen horses diagnosed with nonseptic osteitis of the axial border of a PSB between 2007 and 2012 were reviewed retrospectively. Case details, clinical examination, radiographic, ultrasonographic, computed tomographic and intra‐arterial/intra‐articular contrast‐enhanced computed tomographic features were recorded, when available. Radiographic, ultrasonographic and computed tomographic evaluations of the fetlock region had been performed on 18, 15 and 9 horses, respectively. The effect of the degree of lysis on the grade and duration of lameness was determined. Results All horses had chronic unilateral lameness, 4 with forelimb and 14 with hindlimb signs. On radiographs, lysis was identified in both PSBs in 14 horses, one PSB in 3 horses and in one horse no lysis was identified. The degree of osteolysis was variable. Ultrasonography identified variably sized irregularities of the bone surface and alteration in echogenicity of the palmar/plantar ligament (PL). All horses undergoing computed tomographic examination (n = 9) had biaxial lysis. The lesions were significantly longer and deeper on computed tomographic images compared with radiographic images. Intra‐arterial contrast‐enhanced computed tomography may reveal moderate to marked contrast enhancement of the PL. There was no significant effect of the degree of lysis on the grade and duration of lameness. Conclusions Lesions of nonseptic axial osteitis of a PSB can be identified using a combination of radiography and ultrasonography. Computed tomography provides additional information regarding the extent of the pathology.